Retracts in equiconnected spaces - Jin Ho Kwak; Jaeun Lee (International Journal of Mathematics and Mathematical Sciences)
The object of this paper is to show that the concepts retract and strong deformation retract coincide for a subset of an equiconnected space. Also, we have a similar local version in a locally equiconnected space.